Learner Acceptance and Student Experience of Virtual Reality Usage in Biology learning: A Meta-analysis (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Virtual Reality (VR) technology has become a popular interactive learning medium in the past decade. In sciencelearning, VR has been used to help the learning process in high school. This report presents strong and responsivesurvey results on the satisfaction level and experience of using VR technology in biology learning in high school.With PRISMA guidelines, we analyze the research results on VR use in international databases, namely SAGE,Emerald, Wiley, Springer, Taylor &Francis, ScienceDirect, BMC Medical Education and Elsevier. A total of 13studies were selected for final analysis. The main inclusion criteria are studies that report satisfaction levels anduser experience at the high school level. This study shows that VR provides positive feedback, where VR becomesa valuable tool in the process of biological learning and shows substantial opportunities and has hands-onexperiences that are not possible in the real world. This literature review is important to highlight more researchneeds in a virtual VR-based design learning environment.